Architecture of the two metal-binding sites in prolactin - Vang, Janus; Pustovalova, Yulia; Korzhnev, Dmitry M.; Gorbatyuk, Oksana; Keeler, Camille; Hodsdon, Michael E.; Hoch, Jeffrey C. (Biophysical journal, 2022)
Metal binding by members of the growth hormone (GH) family of hematopoietic cytokines has been a subject of considerable interest. However, beyond appreciation of its role in reversible packing of GH proteins in secretory granules, the molecular mechanisms of metal binding and granule formation remain poorly understood. Here, we investigate metal binding by a GH family member prolactin (PRL) using paramagnetic metal titration and chelation experiments. Cu2+-mediated paramagnetic relaxation enhancement measurements identified two partial metal-binding sites on the opposite faces of PRL composed of residues H30/H180 and E93/H97, respectively. Coordination of metal ions by these two sites causes formation of inter-molecular bridges between the PRL protomers and enables formation of reversible higher aggregates. These findings in vitro suggest a model for reversible packaging of PRL in secretory granules. The proposed mechanism of metal-promoted PRL aggregation lends insight and support to the previously suggested role of metal coordination in secretory granule formation by GH proteins.